Casimir effect in quantum field theory (2023)
In this work, the main characteristics of Quantum Field Theory in flat spacetimes and the Casimir effect are presented. In particular, the physical nature of the Casimir effect proposed by Bernard S. Kay in 1979 was explored, suggesting that this phenomenon is essentially related to flat spacetimes rather than the gravitational context. To accomplish this, the Casimir energy was studied under topological variations of Minkowski spacetime. As a first step towards future work, all the necessary physical and mathematical tools were developed for the analysis of this phenomenon under different approaches. Specifically, the quantization of various physical fields, regularization, and renormalization of both the zeta function and energy densities were addressed.